Growth Hormone Inhibition of Glucose Uptake in Adipocytes Occurs without Affecting GLUT4 Translocation through an Insulin Receptor Substrate-2-Phosphatidylinositol 3-Kinase-dependent Pathway - Sasaki-Suzuki, Naoko (American Society for Biochemistry and Molecular Biology, 2009)
Growth hormone (GH) pretreatment of 3T3-L1 adipocytes resulted in a concentration- and time-dependent inhibition of insulin-stimulated glucose uptake. Surprisingly, this occurred without significant effect on insulin-stimulated glucose transporter (GLUT) 4 translocation or fusion with the plasma membrane. In parallel, the inhibitory actions of chronic GH pretreatment also impaired insulin-dependent activation of phosphatidylinositol (PI) 3-kinase bound to insulin receptor substrate (IRS)-2 but not to IRS-1. In addition, insulin-stimulated Akt phosphorylation was inhibited by GH pretreatment. In contrast, overexpression of IRS-2 or expression of a constitutively active Akt mutant prevented the GH-induced insulin resistance of glucose uptake. Moreover, small interfering RNA-mediated IRS-2 knockdown also inhibited insulin-stimulated Akt activation and glucose uptake without affecting GLUT4 translocation and plasma membrane fusion. Together, these data support a model in which chronic GH stimulation inhibits insulin-dependent activation of phosphatidylinositol 3-kinase through a specific interaction of phosphatidylinositol 3-kinase bound to IRS-2. This inhibition leads to suppression of Akt activation coupled to glucose transport activity but not translocation or plasma membrane fusion of GLUT4.